Lessons in colour - Au, Nicole Jun Wen (Nanyang Technological University, 2023)
Colour is one of the most influential tools in design, with the ability to influence the way one perceives and interprets the world. Being such an integral subject, the symbolism of colour is frequently thought to be knowledge that designers should be familiar with. Yet a designer’s understanding of colour is often limited to the colour theory taught in schools. Colour is also often understood through the theories and practices of people with normal colour vision. While this is not wrong, it is important to acknowledge that the meanings of colours extend beyond what is taught in textbooks or in educational materials. Each individual's perception of colour is highly unique and subjective, and designers could benefit from gaining a new perspective that could demonstrate the vast richness of colours and their symbolism.